Pengalaman Belajar Universitas Selama Disrupsi Pandemi di UIN Antasari Banjarmasin - M. Daud Yahya; Tamjidnor Tamjidnor; Emy Yunita Rahma Pratiwi; Abd. Basir; Akhmad Syahbudin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The focus of this research reveals about the learning experience at one of the Islamic universities in Indonesia, namely UIN Antasari Banjarmasin. This type of research is qualitative with a phenomenological approach. The collection technique uses interviews, observation and documentation. Interviews were conducted with several lecturers and students to obtain data that can answer the problems of this research. Then we have interview data with in-depth evaluation and interpretation to understand how the learning experience, especially distance learning, and all the problems that arise and solutions are solved. The results showed that the learning experience experienced by students contained challenges and opportunities. The challenge was the sudden closure of face-to-face classes, so there was a lack of preparation in many ways. Meanwhile, the opportunity for academics and students to get used to self-study (an important part of higher education culture) since the lecture was closed, however, distance classes were opened. It is hoped that the results of this study can be useful for many parties, especially in making teaching decisions in universities.